Influencia del refuerzo al cortante en la rigidez de vigas de concreto armado - Burgos Obeso, Juan Pablo (2019)
In the present investigation, the importance of correctly estimating the stiffness of the shear of reinforced concrete beams was taken into account, taking into account the effect of the shear fortune on the rigidity in reinforced concrete beams, on the other hand the rigidity was determined. obtained by testing a beam an experimental reinforced concrete beam with reinforcements at different distances of 4, 7, 9 and 11 cm. The rigidity in the experimental shear of a reinforced concrete beam and elaborated under the norm. To evaluate these hypotheses, samples formed by 4 groups were evaluated, each one of 5 reinforced concrete prismatic beams, with abutment separations of 4, 7, 9 and 11 cm respectively for each group. The samples were subjected to a 3-point bending test; using the 60-ton Tecno Test test machine and the effort and displacements were obtained for each instant of the test. We observed the version coded as V-01 elaborated with data of ¼ "placed in spaces of 4 cm obtained a greater rigidity to the bending to the difference of the other beams. This indicates the direct relationship that exists in the shear reinforcement versus rigidity. On the other hand, the effective stiffness from the secant value generated by the graphs in a linear expression, having this stiffness before and after the creep occurs once the flow limit has been exceeded, determining a remarkable reduction of approximately 80% of the initial stiffness. vii